2021
DOI: 10.21776/ub.apmba.2021.010.01.2
|View full text |Cite
|
Sign up to set email alerts
|

Guest Satisfaction on Star Hotel Preparedness In New Normal Era of Covid-19

Abstract: Implementing health protocols is one of the hotel industry's survival strategies in response to the Covid-19 pandemic. Although many studies have examined the importance of management strategies in dealing with disasters in the context of the Covid-19, there has been no study analyse the level of guest satisfaction on the preparedness of star hotels during the 'New Normal Era in Bandung, West Java. This research was conducted to evaluate guest satisfaction on star hotels' preparedness by collecting data from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…On the other hand, FEMA (2003) defines preparedness as a collection of aspects, including hazard awareness, coordination, hazard mitigation, operations, procedures, communications, facilities, and logistics during a crisis. Research conducted by Ervina et al (2021) shows that guest satisfaction concerning hotel preparedness is exceptionally high. The preparedness of each hotel section was examined, but the effect of the preparedness variable on overall guest satisfaction was not examined in detail.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, FEMA (2003) defines preparedness as a collection of aspects, including hazard awareness, coordination, hazard mitigation, operations, procedures, communications, facilities, and logistics during a crisis. Research conducted by Ervina et al (2021) shows that guest satisfaction concerning hotel preparedness is exceptionally high. The preparedness of each hotel section was examined, but the effect of the preparedness variable on overall guest satisfaction was not examined in detail.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…While the study on hotel satisfaction during COVID-19 was reviewed by (Hong et al, 2020), the study's findings indicated that there was a level of change in hotel guest satisfaction, particularly in Bed & Breakfast (B&B) type hotels, between pre-and post-Covid-19 conditions, which has implications for the hotel's marketing strategy. The study (Ervina et al, 2021) explains that preparedness contributes to guest satisfaction but does not examine the relationship between the two variables.…”
Section: Introductionmentioning
confidence: 99%
“…A critique revealed that there is a gap in the SERVQUAL model that is adapted to the framework of the study, it focuses on the discrepancies between consumer expectations and the service provider's assessment of customer demands, according to SERVQUAL model, in the study of Wang et al (2021), the revisit intentions of the lodgers are included in the framework, while this is not found in the model used in this study. According to Ervina et al (2021), service is linked to satisfaction wherein the fundamental to tourism marketing strategy is satisfaction as a marketing tool. There was a shift in consumer orientation, health, and cleanliness aspects during the pandemic, and it became a consideration for staying guests when choosing a hotel, this statement agrees with the concept written in our study.…”
Section: Related Riterature Reviewmentioning
confidence: 99%
“…In the new normal, hotel customers will influence their desire to stay in a hotel depending on the health standards as studied by Fexco Official Portal (2020). As mentioned by Ervina et al (2021), one of the survival measures of hotels in the face of the Covid-19 outbreak is to implement health protocols. With this, the research has concluded that a hotel's preparedness has an essential role in the hospitality industry.…”
Section: Related Riterature Reviewmentioning
confidence: 99%
“…Therefore, management strategies must conform to and fight against the crisis. In addition, Ervina et al (2021) argued that one of the hotel's essential roles in reviving the COVID-19 is managing preparedness. On the other hand, employees also need to understand the unstable condition of the hotel.…”
Section: The Role Of Governmentmentioning
confidence: 99%